2002
DOI: 10.1207/153744202320802142
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Affectivity in Children: A Multitrait-Multimethod Investigation

Abstract: Examined the validity of the tripartite model of anxiety and depression and its internal structure in children. Measures of positive affect/surgency (PA/S) and negative affect/neuroticism (NA/N) and self-report and peer nominations of symptoms of depression and anxiety were completed by 104 children (mean age = 14.9 years, SD = 1.9). Parents completed measures of temperament and anxious and depressive symptoms. Multitrait-multimethod and confirmatory factor analyses (CFA) supported a 3-factor model that includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 0 publications
3
30
0
Order By: Relevance
“…Although authors of some studies have suggested that it is the overlap between selfand others-ratings that provides a more valid index of these characteristics of children (e.g., Cole et al 1997;Rowe and Kandel 1997), we believe that the evidence does not support this assertion. Specifically, in an earlier study in which youth-and parent-report temperament and symptoms were investigated, Phillips et al (2002) found little overlap between youth-and parent-report of children's and adolescent's NA. Additionally, parents' reports of their children's NAwere not correlated with their children's reports of anxiety.…”
Section: Bias In Msmentioning
confidence: 89%
“…Although authors of some studies have suggested that it is the overlap between selfand others-ratings that provides a more valid index of these characteristics of children (e.g., Cole et al 1997;Rowe and Kandel 1997), we believe that the evidence does not support this assertion. Specifically, in an earlier study in which youth-and parent-report temperament and symptoms were investigated, Phillips et al (2002) found little overlap between youth-and parent-report of children's and adolescent's NA. Additionally, parents' reports of their children's NAwere not correlated with their children's reports of anxiety.…”
Section: Bias In Msmentioning
confidence: 89%
“…Briefly, negative affectivity is similar to the BIS, positive affectivity is akin to the BAS, whereas physiological hyperarousal shows clear overlap with the fight/flight system. There is increasing support for the applicability of the tripartite theory to child populations (Chorpita, Daleiden, Moffitt, Yim, & Umemoto, 2000;Laurent et al, 1999), and this evidence converges on the notion that negative affectivity corresponds with neuroticism, whereas positive affectivity matches with extraversion (Phillips, Lonigan, Driscoll, & Hooe, 2002).…”
Section: Temperamentmentioning
confidence: 91%
“…More specifically, the age distribution was as follows: 18.9, 19.7, 16.8, 16, 11.3, 11.8 and 5.5% for age 8,9,10,11,12,13, and 14 respectively. From this total sample, 75.7% (n = 184) participated in wave 2 and 24.3% (n = 59) did not participate in wave 2.…”
Section: Referred Samplementioning
confidence: 99%